Effect Of Zinc Supplementation On The Morphology And Permeability Of The Small Intestine Mucosa Secondary To Chronic Mild Stress In Rats - Saudi, Wan Salman Wan (2010)
Psycho-physiological stress has widely attracted researchers to investigate the effects of stress on physiological system. However, no study about the beneficial role of zinc in stress-induced physiological alterations has been established. Hence, this study examines the effect of zinc supplementation on the physiological parameters, morphology, permeability and inflammatory cell infiltration of the small intestine mucosa secondary to chronic mild stress in rats. 40 male Sprague Dawley rats aged 6 weeks with a mean body weight of 149.69 ± 3.92 g were divided into 4 groups (n=10 for each group); control (C), control with zinc supplement (CZ), stress (S) and stress with zinc supplement (SZ) groups. Water avoidance stress for 1 hour was given daily for 10 consecutive days. Body weight gain, food and water intake and number of stool pellet after every stress session were documented throughout the study. On the 11th day, after overnight fasting, rats were anesthetized with diethyl-ether and fluorescein isothiocyanate dextran solution was injected into small intestinal loop. One hour later, rats were re-anesthetized and blood was collected from the abdominal aorta to measure the intestinal permeability. Rats were sacrificed and ileum and jejunum were taken for histological evaluation and inflammatory cell assay. Statistical comparisons were made by one-way analysis of variance, followed by Post Hoc Tukey test. Daily stress sessions in this study had significantly reduced the body weight gain of S group as compared to C group, although no significant difference was seen in the same groups‟ comparison of food and water intake.